O DIREITO FUNDAMENTAL AO DESPORTO PARA TODOS NO ÂMBITO DA UNIÃO EUROPEIA E O PRINCÍPIO DA SUBSIDIARIEDADE (Revista Lusófona de Economia e Gestão das Organizações, 2021)
The right to practice sports in Portuguese territory, as stipulated in art. 79 of our Constitution of the Portuguese Republic, it is effectively since 1976 and according to a determined political, constitutional and legislative evolution, a fundamental right of all citizens who are in this geopolitical area, in a perspective of universality and equality, as well as, from the outset, a economic, social and cultural law to which everyone should have access. It is, therefore, a legal-constitutional end in itself, a producer of quality of life and well-being, but similarly an optimum means for the most propitious attainment of other fundamental rights and from where health, education, housing and respective infrastructures, social integration or even sustainable environmental development and spatial planning, functioning as well as a driving effect for the appropriate acquisition of these other fundamental pillars. In this way, it provides several benefits, and its relevance has been increased over the seasons, as shown in this scientific work, both nationally but also internationally and mainly European, and therefore, in our opinion, it should fit as a fundamental pillar alongside of the various ones explained here. However, we do not limit ourselves in this investigation to presenting its legal and dogmatic content in Portugal, and it was our priority purpose to study in a very complete way what happened about this “sport for all” right in other European territories, which includes the conducting a comparative analysis of the existing models there and, also as a complement, of the Portuguese-speaking territories. To carry out this investigation, we analyzed the study contained in the Eurobarometer in detail, and several inconsistencies were detected in the development of this right due to the diversity of the Member States. Consequently, our main intention with everything that has been done and mentioned here, has centered on the perception of the disciplinary treaties of the European Union and in particular of the Treaty of Lisbon in relation to the rules of a sporting character. In order to be able to understand the competences attributed to the Union in defense of citizens residing in the Member States and whether it will enjoy the legal possibility of intervention before them, in situations of insufficient propagation of “sport for all” in their respective territories. Since we subsequently made some recommendations based on the principle of subsidiarity so that there is a harmonization of National Legal Orders with European Union Law and which, in our eyesight, are essential so that “sport for all” does not continue to be simply a utopian law in some regions. However, while taking care to safeguard the necessary respect of these geopolitical areas for their sovereignty and national identity.Keywords: Sport for All, Fundamental Law, Portuguese State, European Union, Treaty of Lisbon, Attributions and Competences, Subsidiarity Principle.